Hibiscus schizopetalus as saponin source, reduce protozoa number and increase microbial protein synthesis on in vitro sheep rumen fermentation - Kurniawati, Asih; Umami, Nafiatul (2010)
ABSTRACT : Effect of Hibiscus schizopetalus leaf as saponin source on rumen feed fermentation of sheep was studied using in-vitro gas production techniques. Grounded Hibiscus schizopetalus leaf equal to level of saponin 0%, 0.1%, 0.2%, 0.3% and 0.6% of feed dry matter (DM) was added to feed substrate of king grass and concentrate diet of (60:40), in the expense of king grass. Incubation was done at 39oC for 48 hours. Protozoa number was significantly reduced (P<0.05) in line with increasing saponin level. Increasing saponin levels increased microbial protein (P<0.01) and gas production (P<0.05). The level of saponin at 0.6%DM resulted the lowest protozoa number, the highest microbial protein synthesis and the highest gas production. VFA concentration, ammonia concentration and pH of medium after 48 h fermentation on the other hand were not affected by the treatment. It could be concluded that the addition of saponin from Hibiscus schizopetalus up to level 0.6% of feed DM gave the positive effect on rumen feed fermentation. Keys words: hibiscus schizopetalus, saponin, protozoa, microbial protein, rumen fermentation, in vitro